2023
DOI: 10.1186/s12943-023-01813-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and metabolic regulation of immunosuppression in metastatic pancreatic ductal adenocarcinoma

Abstract: Immunosuppression is a hallmark of pancreatic ductal adenocarcinoma (PDAC), contributing to early metastasis and poor patient survival. Compared to the localized tumors, current standard-of-care therapies have failed to improve the survival of patients with metastatic PDAC, that necessecitates exploration of novel therapeutic approaches. While immunotherapies such as immune checkpoint blockade (ICB) and therapeutic vaccines have emerged as promising treatment modalities in certain cancers, limited responses ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 339 publications
0
5
0
Order By: Relevance
“…[ 26 ] SII level reflects the inflammatory activation status and is a routinely used biomarker of systemic inflammatory activity. [ 27 , 28 ] Patients exhibiting elevated SII levels often develop neutrophilia, thrombocytosis, or lymphocytopenia. Increased secretion of pro-inflammatory cytokines, neutrophil aggregation, and impaired alveolar-capillary barriers may contribute to the pathogenesis of vertebral fractures.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] SII level reflects the inflammatory activation status and is a routinely used biomarker of systemic inflammatory activity. [ 27 , 28 ] Patients exhibiting elevated SII levels often develop neutrophilia, thrombocytosis, or lymphocytopenia. Increased secretion of pro-inflammatory cytokines, neutrophil aggregation, and impaired alveolar-capillary barriers may contribute to the pathogenesis of vertebral fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The premetastatic niche plays a crucial role in facilitating the colonisation of cancer cells in distant organs, 39 and has also has attracted much attention in cancer‐targeting treatment. 40 , 41 Premetastatic niches, which are the foundation of tumour metastasis, are no longer considered to take place in one location. Circulating tumour cells are captured and vascular permeability is increased.…”
Section: Net and Tumour Evolutionmentioning
confidence: 99%
“…Immunosuppression is a hallmark of PDAC which contributes to early metastasis and poor patient survival. Substantial investigations have indicated that PDAC-secreted exosomes could induce the formation of PMNs in the liver, the most common site for PDAC metastasis, through molecular and metabolic regulation of immunosuppression [ 286 , 287 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%